EFFICACY OF USING A MOBILE APPLICATION IN SUPPORT OF POST DISCHARGE COMPLIANCE AMONG HEART FAILURE PATIENTS - Emelia Asamoah, Ph.D. MS, RN (Elsevier, 2023)
Therapeutic Area: Heart Failure Background: Heart failure (HF) self-care management after discharge continues to be a challenge, with increasing hospital readmissions within 30 days. Research is limited in using mobile health applications to improve HF self-care management. Methods: This study relied on an experimental prospective mixed method design triangulation. Researchers selected patients scheduled to follow up with the cardiologist during February or March of 2021 after discharge. Participants were randomized into either the experimental group (n = 20) used the HFHS application or the control group (n = 20) used discharge notes. Demographics, clinical characteristics, pretest, and post-test data were analyzed with differences between the control and experimental groups. Results: Chi-square tests indicated no significant difference between the groups in sociodemographic and clinical characteristics, except one variable (underlying diseases) showed a significant difference (χ2 = 9.294, p = .010). The quantitative analysis based on the pretest results showed no significant differences between the groups. The post-test survey measured the effect of the independent variable (intervention type-HFHS application versus discharge instructions) on the outcome variables related to weight, medication, physical activity, low sodium diet, fluid, swelling, keeping medical appointments, obtaining information about health and reducing salt intake when short of breath, calling the doctor when short of breath, following treatment advice, and recognizing changes in health. The post-test results indicated notable differences between groups except for two variables (calling a doctor when short of breath and checking swelling), which showed no significance with a (χ2 = 5.796, p = .055) and (χ2 = 5.767, p = .050) respectively. The qualitative findings revealed differences between the control and experimental groups. Conclusions: The HFHS application is effective at assisting self-care maintenance and management after discharge in patients with HF. Use of application must supplement discharge instructions to improve patients' confidence in their ability to maintain and manage self-care.